Presence and persistence of hepatitis E virus RNA and proteins in human bone marrow - Lin Wang; Li Yan; Jieling Jiang; Yuyi Zhang; Qiyu He; Hui Zhuang; Ling Wang (Emerging Microbes and Infections)
Hepatitis E virus (HEV) infection is primarily manifesting as acute hepatitis, but extra-hepatic replication and injury are frequently reported. During the study period, we discovered two acute myeloid leukaemia (AML) patients infected with HEV genotype 3 and 4, respectively, and HEV RNA and/or viral proteins were persistently detected in the bone marrow of both patients. The finding suggests that HEV can replicate in human bone marrow as it may serve as a new target site and reservoir of HEV persistence.